Organic cotton network in Brazil addressing textile and clothing sector - Duarte, Larissa Oliveira (2020)
Organic cotton is the main eco-material used by sustainable clothing brands. At the same time, cotton cultivation is of great economic importance in Brazil, as it can be cultivated in various climatic and soil conditions. The Brazilian textile and clothing sector covers the entire chain, from the production of raw materials, to the production of yarns and textiles, manufacture of clothing, distribution, marketing, retail and customers. However, even though the country is the fourth largest international producer of traditional cotton, organic farming still has a limited volume. Despite being a demanding fiber in the market, there is a gap in the understanding of its network, which may be hindering its potential development. The aim of this study was to identify the main actors and develop a description of the organic cotton network in Brazil. A literature review, interviews and technical visits in the states of Minas Gerais, Paraíba and São Paulo and analysis of annual cotton reports by national and international organizations were carried out. Interest in the production of organic cotton has been increasing every year, but producers still face difficulties in articulating with the market, both in the production and in the commercialization of organic cotton fiber. EMBRAPA Cotton, Laudes Foundation and VEJA represent the central positions in the analysis of organic cotton networks. This is followed by NGOs such as Diaconia, Arribaçã, Esplar and Textile Exchange, the companies OCC, NCC and Justa Trama and the public research institution EMPAER. The lack of a social organization or a company was noticed, to play the role of connection between producers and the textile industry in Brazil\'s organic cotton network. National and international NGOs open spaces for sharing value and exchanging information and play the role of financing agroecological projects in Brazil, supporting the structural consolidation of the network. Brands and retailers also have a crucial role to play, as they have the capacity to pull the sector towards greater sustainability, demanding and buying organic cotton